SUATU KAJIAN MOLEKULER KETERGANTUNGAN NIKOTIN - Agustina Setiawati (Universitas Sanata Dharma, 2016)
Abstract: Nicotine, a simple chemical substance from tobacco, stimulates addiction by neuroadaptation inducing rewards system in human brain. Molecular mechanism of nicotine addiction in rewards system are mediated by nicotinic acetylcholine receptor (nAChR) and activate dopaminergic neuron. Thus, nicotine addiction are also induce other neurottransmitter and hormone release: norephinefrin, serotonin, opioid, glutamat and mono amine oxidase. Keywords: nicotine, addiction, rewards system.